That is also nation-building. Football and Francoism in Catalonia and the Basque Country (1939-1977) - Quiroga Fernández de Soto, Alejandro (Hispania Nova, 2019)
This article analyses the Franco dictatorship’s uses of F. C. Barcelona and Athletic Bilbao to nationalize Catalans and Basques on Spanish principles. Following the Spanish Civil War, both F. C. Barcelona and Athletic Bilbao were turned into propaganda devices of a regionalized Francoist nationalism where Catalans and Basques were presented as key groups of the ’New Spain’. The article challenges the idea that the Franco regime sought to annihilate all vestiges of regional identities in the first years of the dictatorship. The paper also questions the notion that Francoist nationalism somehow weakened in the last years of the dictatorship, as the display of Catalan and Basque nationalism grew in the stadiums of F. C. Barcelona and Athletic Bilbao.